1998
DOI: 10.1073/pnas.95.25.14646
|View full text |Cite
|
Sign up to set email alerts
|

Differential use of the signal recognition particle translocase targeting pathway for inner membrane protein assembly in Escherichia coli

Abstract: Assembly of several inner membrane proteins-leader peptidase (Lep), a Lep derivative (Lep-inv) that inserts with an inverted topology compared with the wild-type protein, the phage M13 procoat protein, and a procoat derivative (H1-procoat) with the hydrophobic core of the signal peptide replaced by a stretch from the first transmembrane segment in Lep-has been studied in vitro and in Escherichia coli strains that are conditional for the expression of either the 54 homologue (Ffh) or 4.5S RNA, which are the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 56 publications
3
128
1
2
Order By: Relevance
“…The extent to which precursor proteins accumulated in the absence of Ffh, relative to accumulation in the presence of Ffh, increased as the hydrophobicity of signal sequences decreased. Recent evidence [19] suggested that preproteins with more hydrophobic signal sequences would be more a¡ected by depleting Ffh. Interestingly, these results suggest that the role of SRP is not restricted to the transport of precursor proteins with very hydrophobic signal sequences or membrane proteins, but it is also responsible for the transport of proteins that have relatively weak hydrophobic signal sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which precursor proteins accumulated in the absence of Ffh, relative to accumulation in the presence of Ffh, increased as the hydrophobicity of signal sequences decreased. Recent evidence [19] suggested that preproteins with more hydrophobic signal sequences would be more a¡ected by depleting Ffh. Interestingly, these results suggest that the role of SRP is not restricted to the transport of precursor proteins with very hydrophobic signal sequences or membrane proteins, but it is also responsible for the transport of proteins that have relatively weak hydrophobic signal sequences.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, maltose binding protein (MBP) and OmpA are normally targeted to the IM by SecB, but increasing the net hydrophobicity of their signal peptides reroutes both proteins into the SRP pathway (18). Furthermore, the biogenesis of M13 procoat protein, a small IMP whose insertion normally does not require any targeting factor, becomes SRP-dependent when it contains an unusually hydrophobic signal peptide (19). Likewise, yeast SRP binds preferentially to signal peptides that have a high hydrophobicity index (20).…”
Section: The Signal Recognition Particle (Srp)mentioning
confidence: 99%
“…In Escherichia coli, polytopic membrane protein insertion seems to require the secretory translocase (8)(9)(10) as well as other proteins needed for insertion in eukaryotes, such as the signal recognition particle (10,11). In addition, insertion of E. coli polytopic membrane proteins in vitro occurs cotranslationally (12)(13)(14). Thus, the mechanism of polytopic membrane protein insertion in E. coli and other prokaryotes may be universally relevant.…”
mentioning
confidence: 99%